A Comparison of Hemoglobin A2 Levels in Untreated and Treated Groups of HIV Patients on ART Including Zidovudine. (26th December 2013) - Nigam, Jitendra Singh; Bharti, Jyotsna Naresh; Kumar, Dinker; Sharma, Ankit
Abstract : Objective . To assess the level of haemoglobin A2 in HIV patients on antiretroviral therapy (ART) including zidovudine with untreated HIV patients. Material and Methods . The study was a case control study. A total of 185 patients were included in the study; the case group included 125 HIV patients who were on antiretroviral therapy (ART) including zidovudine and 60 were in the control group who were not receiving ART. The high-performance liquid chromatography (HPLC) was done and hemoglobin A2 level was observed; value more than 3.5% was considered significant. The Hb A2 percentages of HIV patients were compared with those of control using an unpaired t -test. Results. The mean of Hb A2 in case group was 3.462% (SD 0.675) and in control group it was 2.815% (SD0.246). The higher Hb A2 value was seen in significant number of treated patients than control group (P < 0.0001 ). Conclusion. The clinicians, pathologists, haematologists, and genetic counsellors should be aware of effects of nutritional anaemia and ART on Hb A2 to reduce the chances of misdiagnosis of β -thalassaemia especially in developing countries and for centres for antenatal screening.